SOSIALISASI DAN PELATIHAN PEMBUATAN PUPUK ORGANIK CAIR DARI LIMBAH KULIT PISANG DAN IMPLEMENTASIKAN PADA TANAMAN PAKCOY (Brassica Rapa L ) DI DESA TEBING TINGGI PANGAKATAN KABUPATEN LABUHAN BATU SUMATERA UTARA - Rayyan Rayyan; Khairul Rizal; Kamsia Dorliana Sitanggang; Hilwa Walida (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
Pakcoy (Brassica rapa L.) is a type of mustard that is quite economical. Currently, the pakcoy plant is used by the community in various dishes. This plant is quite easy to cultivate and only requires a short time of about 3-4 weeks. The aim is to obtain data on the growth response and production of pakcoy plants to the application of liquid organic fertilizer banana peels. Liquid fertilizer is a fertilizer whose basic ingredients are animals and plants that have been undergoes fermentation and the product form is in the form of liquid, one of which is banana peel waste which is used for the manufacture of liquid fertilizer because it contains micro elements N, P and K. Because many people process processed production from bananas which always produce banana peel waste in processing the waste is only disposed of and left to pile up by the community, if not handled quickly it will produce an unpleasant odor so that it will pollute the environment, one alternative is the service team invites socialization and training to the community by processing the banana peel waste into liquid organic fertilizer with the fermentation process tation, so that people can use liquid organic fertilizers instead of using chemical fertilizers that are more expensive for all plantation crops.